Association Between Hemodynamic Profile, Physical Capacity and Quality of Life in Pulmonary Hypertension - Torres,Diego de Faria Magalhães (2015)
Background: No studies have described and evaluated the association between hemodynamics, physical limitations and quality of life in patients with pulmonary hypertension (PH) without concomitant cardiovascular or respiratory disease. Objective: To describe the hemodynamic profile, quality of life and physical capacity of patients with PH from groups I and IV and to study the association between these outcomes. Methods: Cross-sectional study of patients with PH from clinical groups I and IV and functional classes II and III undergoing the following assessments: hemodynamics, exercise tolerance and quality of life. Results: This study assessed 20 patients with a mean age of 46.8 ± 14.3 years. They had pulmonary capillary wedge pressure of 10.5 ± 3.7 mm Hg, 6-minute walk distance test (6MWDT) of 463 ± 78 m, oxygen consumption at peak exercise of 12.9 ± 4.3 mLO2.kg-1.min-1 and scores of quality of life domains < 60%. There were associations between cardiac index (CI) and ventilatory equivalent for CO2 (r=-0.59, p <0.01), IC and ventilatory equivalent for oxygen (r=-0.49, p<0.05), right atrial pressure (RAP) and 'general health perception' domain (r=-0.61, p<0.01), RAP and 6MWTD (r=-0.49, p<0.05), pulmonary vascular resistance (PVR) and 'physical functioning' domain (r=-0.56, p<0.01), PVR and 6MWTD (r=-0.49, p<0.05) and PVR index and physical capacity (r=-0.51, p<0.01). Conclusion: Patients with PH from groups I and IV and functional classes II and III exhibit a reduction in physical capacity and in the physical and mental components of quality of life. The hemodynamic variables CI, diastolic pulmonary arterial pressure, RAP, PVR and PVR index are associated with exercise tolerance and quality of life domains.